FAKTOR RESIKO YANG MENYEBABKAN KEJADIAN GIZI LEBIH PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT USU TAHUN 2014 - TRESA DAMANIK; Evawany Y Aritonang; Mhd.Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Overnutrition is a unbalance condition between intake energy and output energy. Overnutrition known as overweight or obesity. According to the healthy research database (2013), prevalence of overnutriton in Indonesia increase from 2010 to 2013 that is 10 % become 13,5%. Result of research by Lestari in Medicine Faculty USU in 2012 showed 20,1% prevalence of overweight and obesity with the risk factor namely high supply of protein, fat an carbohydrate. This research is to know the risk factor caused overnutrution to student of public health faculty at USU. Conducted research using case control design. The aim of this research is to know relathionship among genetic, pattern of consumption, and physical activity with incidence of overnutrition. The sample for this study were 64 students of 2010-2012 years . 32 for case group and 32 for control group selected through purposive sampling technique. Univariate data namely age, sex, houselife, job of parents were analyzed descriptively and bivariate data namely genetic, pattern of consumption, and physical activity were analyzed using the chi square test with 95% CI. The data were collected by used food recall 24 hour form and physical activity form. The result of bivariate analysis showed relationship between genetic (p=0,005;OR=2,006), father’s nutrition status (p=0,019;OR=2,003), mother’s nutrition status (p = 0,001;OR=2,468),  protein supply (p = 0,009), fat supply (p = 0,042), carbohydrate supply (p = 0,010) and physical activity (p = 0,045;OR=7,154) with the incidence of overnutrition. And there is no relationship between frequency of eating with the incidence of overnutrition (p=0,157) It was recommended for the students doing physical activity routinely and consume healthfull food to decrease the incidence of overnutrition Keywords:       Risk Factor, overnutrition, public health